Steatocystoma Multiplex, Treatment With Electrosurgery - A Novel Approach - Lahiri Koushik; Sengupta Sujit R (Wolters Kluwer Medknow Publications, 1998)
Treatment of steatocystoma multiplex with the existing modalities of management, is often cumbersome and, sometimes, frustrating. The incisional, excisional and sclerotic methods, all have their limitations. The proposed technique, in the present study, is an improvisation of the incisinal and excisional methods with some modifications by electro surgical techniques. The result is encouraging in almost all the patients with lesions over different regions of their bodies.